2018
DOI: 10.1007/s00484-018-1597-0
|View full text |Cite
|
Sign up to set email alerts
|

Development of a bioclimatic wind rose tool for assessment of comfort wind resources in Sydney, Australia for 2013 and 2030

Abstract: This study assessed the effect of wind on human thermal comfort by preforming outdoor urban climatic comfort simulations using state-of-the-art heat-balance models of human thermo-physiology (Universal Thermal Climate Index-UTCI). A series of simulations for computing "wind cooling potential" have been performed using the UTCI index temperatures. The comfort cooling effect of wind has been estimated by modelling with wind taken into account, and under calm wind (0.05 m/s) (ΔUTCI). A novel wind rose biometeorol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 21 publications
1
14
0
Order By: Relevance
“…Wind is a significant factor affecting thermal sensation in urban climates (Sadeghi et al, 2018). Ketterer and Matzarakis (2014) indicate that air temperature alone is not an appropriate measure to quantify the intra-urban spatial variability of climate with respect to human thermal comfort.…”
Section: Introductionmentioning
confidence: 99%
“…Wind is a significant factor affecting thermal sensation in urban climates (Sadeghi et al, 2018). Ketterer and Matzarakis (2014) indicate that air temperature alone is not an appropriate measure to quantify the intra-urban spatial variability of climate with respect to human thermal comfort.…”
Section: Introductionmentioning
confidence: 99%
“…The result of the comparison showed that the thresholds calculated in this study conform to what previous studies reported. Particularly, these thresholds calculated in this study do not seem to contradict with wind comfort criteria guideline developed for Melbourne CBD before [30]. The guideline that is based on Melbourne Wind Criteria [31] advised that for different postures, V a values should not be greater than 3 m/s for sitting, 4 standing and 5 m/s for walking individuals.…”
Section: Wind Comfort Sensitivity Thresholdsmentioning
confidence: 57%
“…GWTS [30] has proposed several design options to engineer wind flow for better thermal comfort in Melbourne CBD. Additionally, the adoption of lift-up design for the densely built-up area with high rise buildings is advocated recently by several researchers around the world [11,22,53,54] and this applies to Melbourne's CBD conditions.…”
Section: Geometry and Wind Perceptionsmentioning
confidence: 99%
See 2 more Smart Citations